التناسب بين المواد والطرق في تعليم اللغة الغربية بالمدرسة الثانوية الإسلامية - Hayati, Ulfi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This paper aims to find out the Arabic material and methods used and find out the relationship between the two in learning Arabic in Madrasah Aliyah. The methodology used is correlation, and the results obtained that there is an increased relationship between Arabic language material and the learning method. This shows that the material taught by the teacher is in accordance with the methods used so that the process of learning Arabic becomes effective. Keywords: relevance, subjects, teaching methods